Susceptibility trends and molecular characterization of Gram-negative bacilli associated with urinary tract and intra-abdominal infections in Jordan and Lebanon: SMART 2011–2013. (June 2015) - Hayajneh, Wail A.; Hajj, Aline; Hulliel, Fawzi; Sarkis, Dolla Karam; Irani-Hakimeh, Noha; Kazan, Lama; Badal, Robert E.
Highlights: We report resistance trends in Gram-negative bacilli from Jordan and Lebanon. Urinary tract and intra-abdominal infections occurring between 2011 and 2013 were followed. The overall incidence rate of extended-spectrum beta-lactamases (ESBLs) among pooled Gram-negative bacilli was 44%. CTX-M-15 was the most prevalent ESBL, with many isolates producing multiple enzymes. The prevalence of carbapenem-non-susceptible Enterobacteriaceae was 1.6%. Summary: Objectives: To investigate phenotypic and genotypic patterns of antimicrobial resistance among Gram-negative bacilli associated with urinary tract infection (UTI) and intra-abdominal infection (IAI) in medical centres of Jordan and Lebanon. Methods: Gram-negative bacilli from the SMART study, collected between the years 2011 and 2013, were first identified at local laboratories. These isolates were shipped to a central laboratory where re-identification, susceptibility testing, and molecular characterization were performed using standard methods. Results: Among the 523 UTI-associated isolates, Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis were the most frequent (70%, 14%, and 5%, respectively). E. coli, K. pneumoniae, and Pseudomonas aeruginosa were the most frequent species among the 527 IAI-associated isolates (46%, 14%, and 12%, respectively). Incidence rates of extended-spectrum beta-lactamase (ESBL) producers among UTI-associated E. coli, K. pneumoniae, and P. mirabilis were 43%, 54%, and 4%, respectively. Corresponding rates among IAI-associated isolates were 49%, 56%, and 12%, respectively. Acinetobacter baumannii and P. aeruginosa isolates showed very disturbing low susceptibility patterns. CTX-M-15 was the most prevalent ESBL produced. Seventeen isolates were non-susceptible to carbapenems (estimated prevalence of 1.6%). Conclusions: The alarmingly high rates of ESBL production and emergence of carbapenemases emphasize the urgent need to develop antimicrobial stewardship initiatives and to maintain antimicrobial resistance surveillance systems.